New Perspectives and Challenges in Traffic and Transportation Engineering Supporting Energy Saving in Smart Cities (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book focuses on aspects related to new perspectives and challenges in traffic and transportation engineering supporting energy saving in smart cities. Transportation, like other spheres of human activity, is constantly changing due to economic development. People are constantly improving the ways of moving using various energy sources, expanding infrastructures, and adapting cities to increasing traffic volumes. Many of the contents presented in this book are characterized by a multidisciplinary approach to a global problem. Topics of interest include, but are not limited to, the following: road traffic measurements; data analysis; road traffic (micro-, meso-, macro-) modeling; simulation models; road and intersection capacity; optimization, route choice; human factor in road traffic and transportation engineering; road safety; pedestrian and bicycle traffic and infrastructure; public transportation solutions; parking issues; contemporary problems of road traffic engineering and sustainable transportation; intelligent transportation systems (ITS); traffic control and management; smart grid services; electric mobility; environmental impacts of transportation systems; life cycle analysis (LCA) of alternative energy vectors for road vehicles; transportation systems and process modeling; sustainable transportation development; life cycle impact; fuel consumption; and emissions.